(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Dengue Hemorrhagic Fever (DHF) is a communicable disease caused by the dengue virus (DENV) and transmitted through the bite of Aedes mosquitoes. Arjasa Village, located in Arjasa Sub-district, Jember Regency, is considered a high-risk area for an increase in DHF cases, particularly due to environmental conditions that support vector breeding. This community service activity aimed to improve public knowledge regarding the prevention and control of DHF through educational intervention. The program was implemented through material delivery and interactive discussions, accompanied by pre-test and post-test evaluations to measure changes in understanding. The results showed a significant increase in public knowledge, with the average score rising from 62% before the training to 90% afterward. The effectiveness of the educational activity was assessed using the non-parametric Wilcoxon test to compare participants’ knowledge levels before and after the intervention. The analysis produced a p-value of 0.001, which is below the 0.05 significance level, demonstrating a statistically significant difference between the pre-test and post-test results. This improvement demonstrates the effectiveness of the educational activity in raising awareness about the importance of environmental cleanliness and eliminating mosquito breeding grounds. Therefore, this educational intervention successfully enhanced community understanding and has the potential to encourage sustained active participation in DHF prevention efforts.